Gender – an Issue for Social Organizations in Germany? - Chris Lange (Social Work and Society, 2003)
During the last months and years the English expression ‘gender‘ has become a well-known word all over Germany, often with the annex ‘mainstreaming‘. Gender mainstreaming was initiated as a political strategy by the Women‘s World Conference in Beijing in 1995 and adopted by the European Union in 1997 (COM(96)76 final). It basically means that all actions and initiatives planned have to be tested as to their effects on women and men and should not be taken if they disadvantage either one. But gender is also a category in the discussion about democratic features. Gender democracy means that males and females should be represented equally in the public, political, cultural, social and economic sphere of a society. On this background, this paper traces the gender issue in the field of organizations in the social sector of Germany, in particular the ‘welfare organizations‘. In this article, ‘welfare organizations‘ is used as a translation of the German word ‘Wohlfahrtsverbände‘. The reason for this choice is the endeavor to indicate their difference from for instance English ‘charitable associations‘ or French ‘associations sociale et sanitaire‘, because social organizations in the EU-member states differ considerably in regard to their history, function, self-image , financing, political power etc.. The terms ‘social non-governmental organizations‘ (NGOs) or ‘social nonprofit organizations‘ (NPOs ) are used synonymously.